Ramon Valls (1928-2011): The agonist of «we» - Mayos, Gonçal (Journal of Catalan Intellectual History, 2014)
Like the rest of his generation, Valls was marked by the Spanish Civil War and the Francoist repression. Therefore he viewed humanity from realpolitik, pessimistic and agonistic; he searched to give a philosophical base to an “we” which would end the struggle of one against another. We analyze his attacks on “we” built on class, culture or nationality, civil society o the “I” individual, emotivism or moralism, which are impotent and feed the natural human “agonism”. Instead, Valls first thought he’d found the “we” in the church, but then changed radically and only trusted the Hegelian version of the state. In this article we take a balance of the work and teaching of the recently departed professor. key words War, State, Hegel, Church, Class, Nation, I, Moralism